E-Business 2.0 : Roadmap for Success - Kalakota, Ravi; Robinson, Marcia (Addison-Wesley information technology series., 2000)
Revolutions begin with attacks on the language. Today's managers are bombarded with an alphabet soup of technology acronyms such as CRM, ERP, and SCM. Managers must manage in the fog of this technology revolution. Kalakota and Robinson's book provides a lens for managers who want to understand the terminology and take action--to grasp the opportunities or defend against the invading virtual competitors. When the history of e-business is written--perhaps sooner than we think--this book will go down as a management landmark that helped clear the fog of mumbo jumbo and provided a beacon through which managers could chart their course. --Michael Quinn, eStrategy Director, B2B Commerce Limited To survive and succeed in today's complex business world, all companies--from established industry leaders to feisty upstarts--must develop a strategy that allows them to take maximum advantage of the latest trends in technology. Successful companies have implemented focused e-business strategies to build cutting-edge enterprises that serve and retain customers, manage suppliers, and integrate selling chains better than ever before. Others, unfortunately, are lured into ill-fated ventures by the ever-changing roster of buzzwords, fads and analogies. A timely follow-up to the best-seller on this crucial topic, e-Business 2.0 reveals how managers are rewiring the enterprise to take maximum advantage of e-business. Ravi Kalakota and Marcia Robinson present an innovative application framework that guides the migration from a traditional business model to an e-business model. Drawing on their extensive personal experience working with leading businesses, they provide a clear picture of the benefits and challenges that e-business companies face and identify the fundamental design principles for building a successful e-business blueprint. This new edition incorporates the latest strategies and techniques gained from the experiences of the first generation of e-businesses. In addition to updated information on application framework design, the book now features more detail on strategy and e-business execution. e-Business 2.0 shows how e-commerce has evolved into e-business and identifies the 20 key e-business trends that are shaping today's economy. It then addresses core application frameworks--customer relationship management, selling chain management, enterprise resource planning, supply chain management, e-procurement, and business intelligence--and shows how each f ...